2001
DOI: 10.1107/s0108270100015808
|View full text |Cite
|
Sign up to set email alerts
|

A dinuclear pyrazolato-N:N′-bridged dinickel(II) complex of 1,3-bis(5-chlorosalicylideneamino)propan-2-ol

Abstract: The title compound, "-[1,3-bis(5-chloro-2-oxidobenzylideneamino)propan-2-olato(3À)]-O,N,O H :O H ,N H ,O HH-"-(3,5-dimethylpyrazolato)-N:N H-dinickel(II), [Ni 2 (C 17 H 13 Cl 2 N 2 O 3)(C 5 H 7-N 2)], has crystallographic mirror symmetry. The Ni atoms in the dinuclear structure are linked symmetrically by the N atoms of the 3,5-dimethylpyrazole group and by the alkoxo O atom. Each Ni II ion is coordinated by two N atoms and two O atoms, forming a square plane with trans-N 2 O 2 geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Thus imidazole containing ligands have been used to prepare dinuclear Cu 2ϩ , 3 Ni 2ϩ , 4 and Zn 2ϩ 5 complexes as well as a series of model compounds which mimic superoxide dismutase. 6 Similary pyrazole based ligands can give dinuclear Cu 2ϩ , 7 Ni 2ϩ , 8 and Zn 2ϩ 9 complexes some of which have been proposed as models for tyrosinase and laccase 10 or for urease. 11 The situation for 1,2,4-triazole is somewhat different since this ligand can form dinuclear species using either N 1 and N 2 , 12 the two nitrogen adjacent to each other, or N 1 and N 4 the two distal nitrogens, in the so called "long bridging mode".…”
Section: Introductionmentioning
confidence: 99%
“…Thus imidazole containing ligands have been used to prepare dinuclear Cu 2ϩ , 3 Ni 2ϩ , 4 and Zn 2ϩ 5 complexes as well as a series of model compounds which mimic superoxide dismutase. 6 Similary pyrazole based ligands can give dinuclear Cu 2ϩ , 7 Ni 2ϩ , 8 and Zn 2ϩ 9 complexes some of which have been proposed as models for tyrosinase and laccase 10 or for urease. 11 The situation for 1,2,4-triazole is somewhat different since this ligand can form dinuclear species using either N 1 and N 2 , 12 the two nitrogen adjacent to each other, or N 1 and N 4 the two distal nitrogens, in the so called "long bridging mode".…”
Section: Introductionmentioning
confidence: 99%
“…Ni ( plexes [11,13]. The Ni(l)-0(3)-Ni(2) and Ni(3)-0(8)-Ni(4) angles are 125.6(2)° and 125.5(2)°, respectively.…”
Section: Selected Bond Lengths [A] and Angles [°] Char---------------mentioning
confidence: 97%
“…However, some recent articles have evidenced an increasing interest for emitting Ni II complexes (Srinivas et al, 2016;Cerezo et al, 2017;More et al, 2017b). In the last decade, our research group and others have reported the synthesis, structural, spectroscopic, NLO and magnetic properties of some nickel(II) Schiff base complexes (Elerman et al, 2001;Kara et al, 2003;Ü nver et al, 2006;Shawish et al, 2016;Elmehdawi et al, 2017). According to the Cambridge Structural Database (CSD, Version 5.38, November 2016 updates;Groom et al, 2016), there are few reports on investigations of the emission spectra of salen-type ligands [salen is 2,2 0 -ethylenebis(nitrilomethylidene)diphenol] and their Ni II complexes (More et al, 2017a,b;Donmez et al, 2017a,b).…”
Section: Introductionmentioning
confidence: 97%